Pain and overall quality of life in palliatively treated colorectal cancer patients 1 year after diagnosis– results from the EDIUM cohort - Sophie Klara Schellack; Clara Breidenbach; Christoph Kowalski; Ulrich Wedding; Birgitt van Oorschot; Thomas Seufferlein; Stefan Benz; Martin Schnell; Jörg Köninger; Christina Klein; Johann Ockenga; Björn Freitag; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Diagnosis with UICC stage IV colorectal cancer often indicates palliative treatment to alleviate symptoms. Data on pain in these patients are still scarce but can help improve symptom management. This study therefore aimed to describe patient-reported pain and quality of life. Methods 147 palliatively treated stage IV colorectal cancer patients diagnosed between 2018 and 2023 completed the EORTC QLQ-C30 and QLQ-CR29 before and 12 months after treatment initiation within the EDIUM study. Descriptive results for pain and quality of life were examined and compared to reference values. A logistic regression analysis investigated the relationship between quality of life and pain and 1-year survival. Results The mean (SD) for the “overall pain” score was 26 (32) (T0) and 35 (32) (T1) for rectal cancer patients and 34 (33) (T0) and 35 (32) (T1) for colon cancer patients. This is higher than the reference value (24 (30)) and indicates high average pain levels. The “overall quality of life” score showed means below the reference value (61 (23)), indicating poorer quality of life (colon: 51 (25) (T0), 56 (22) (T1); rectum: 52 (24) (T0), 51 (22) (T1)). Higher pain levels persisted at both time points, with no patients reporting absence of pain. The logistic regression results suggest a small relationship between pain and quality of life and 1-year survival. Discussion This study reveals high levels of pain among palliatively treated colorectal cancer patients, impacting their quality of life. Effective pain management and close monitoring are necessary to improve the quality of life for these patients. Trail number DRKS00008724.